Rare Earth Dopant (Nd, Gd, Dy, and Er) Hybridization in Lithium Tetraborate - Kelly, Tony D.; Petrosky, James C.; McClory, John W.; Adamiv, Volodymyr T.; Burak, Yaroslav V.; Padlyak, Bohdan V.; Teslyuk, Ihor M.; Lu, Ning; Wang, Lu; Mei, Wai-Ning; Dowben, Peter A. (Frontiers in Physics, 2014)
The four dopants (Nd, Gd, Dy, and Er) substitutionally occupy the Li+ sites in lithium tetraborate (Li2B4O7: RE) glasses as determined by analysis of the extended X-ray absorption fine structure. The dopants are coordinated by 6-8 oxygen at a distance of 2.3 to 2.5 Å, depending on the rare earth. The inverse relationship between the RE-O coordination distance and rare earth (RE) atomic number is consistent with the expected lanthanide atomic radial contraction with increased atomic number. Through analysis of the X-ray absorption near edge structure, the rare earth dopants adopt the RE3+ valence state. There are indications of strong rare earth 5d hybridization with the trigonal and tetrahedral formations of BO3 and BO4 based on the determination of the rare earth substitutional Li+ site occupancy from the X-ray absorption near edge structure data. The local oxygen disorder around the RE3+ luminescence centers evident in the structural determination of the various glasses, and the hybridization of the RE3+ dopants with the host may contribute to the asymmetry evident in the luminescence emission spectral lines. The luminescence emission spectra are indeed characteristic of the expected f-to-f transitions; however, there is an observed asymmetry in some emission lines.